Tari Geboy Kembang Buruan di Sanggar Cantika Kabupaten Bandung - Rahayu, Sesi Febi; Narawati, Tati; Badaruddin, Saian (Gesture: Jurnal Seni Tari, 2025)
This study aims to describe and analyze the Geboy Kembang Buruan dance in order to reveal the uniqueness and cultural identity embedded within it. Using a qualitative paradigm with an ethnochoreological approach and descriptive-analytical method, data were collected through observation, interviews, literature review, and documentation. The analysis was conducted using triangulation techniques to obtain a comprehensive understanding of the dance, not only from its aesthetic aspects but also its embedded character values.The results show that textually, this dance consists of nine movement variations, dominated by four gesture movements, four locomotor movements, and three pure movements. Contextually, the dance reflects character traits such as joy and cheerfulness. Geboy Kembang Buruan is categorized as a new creation of Jaipongan dance, representing the emotional and physical journey of a young girl during puberty, with themes of growth, transformation, and the search for identity.This research is expected to enrich the documentation of traditional West Javanese dance arts and contribute to cultural preservation through education, art festivals, and academic studies in the fields of dance and culture.